Treatment with the Ferroptosis Inhibitor Ferrostatin-1 Attenuates Noise-Induced Hearing Loss by Suppressing Ferroptosis and Apoptosis. (7th December 2022) - Ma, Peng-Wei; Wang, Wei-Long; Chen, Jia-Wei; Yuan, Hao; Lu, Pei-Heng; Gao, Wei; Ding, Xue-Rui; Lun, Yu-Qiang; Liang, Rui; He, Zu-Hong; Yang, Qian; Lu, Lian-Jun
Abstract : Hair cell death induced by excessive reactive oxygen species (ROS) has been identified as the major pathogenesis of noise-induced hearing loss (NIHL). Recent studies have demonstrated that cisplatin- and neomycin-induced ototoxicity can be alleviated by ferroptosis inhibitors. However, whether ferroptosis inhibitors have a protective effect against NIHL remains unknown. We investigated the protective effect of the ferroptosis inhibitor ferrostatin-1 (Fer-1) on NIHL in vivo in CBA/J mice and investigated the protective effect of Fer-1 on tert-butyl hydroperoxide (TBHP)-induced hair cell damage in vitro in cochlear explants and HEI-OC1 cells. We observed ROS overload and lipid peroxidation, which led to outer hair cell (OHC) apoptosis and ferroptosis, in the mouse cochlea after noise exposure. The expression level of apoptosis-inducing factor mitochondria-associated 2 (AIFM2) was substantially increased following elevation of the expression of its upstream protein P53 after noise exposure. The ferroptosis inhibitor Fer-1was demonstrated to enter the inner ear after the systemic administration. Administration of Fer-1 significantly alleviated noise-induced auditory threshold elevation and reduced the loss of OHCs, inner hair cell (IHC) ribbon synapses, and auditory nerve fibers (ANFs) caused by noise. Mechanistically, Fer-1 significantly reduced noise- and TBHP-induced lipid peroxidation and iron accumulation in hair cells, alleviating ferroptosis in cochlear cells consequently. Furthermore, Fer-1 treatment decreased the levels of TfR1, P53, and AIFM2. These results suggest that Fer-1 exerted its protective effects by scavenging of ROS and inhibition of TfR1-mediated ferroptosis and P53-AIFM2 signaling pathway-mediated apoptosis. Our findings suggest that Fer-1 is a promising drug for treating NIHL because of its ability to inhibit noise-induced hair cell apoptosis and ferroptosis, opening new avenues for the treatment of NIHL.